Prof. dr. Edward Loth – founder of developmental anatomy in Poland - Odrowąż-Szukiewicz, Halina (Anthropological Review, 1975)
Edward Loth M. D., Ph. D., prominent Polish anatomist and anthropologist studied physical anthropology and related sciences in Zürich (1903–1907) and medicine in Göttingen and Heidelberg (1907–1912). During the First World War he took a part in struggle for independence of Poland as a colonel in medical service of Polish armed forces. In 1915 he had got habilitation at Medical Faculty of Jan Kazimierz University in Lwów, at the end of the same year became a chief of Department of Anatomy at Medical Faculty of Warsaw University where in 1920 got professor's position. He retained this position until beginning of the Second World War. Prof. Loth was an excellent lecturer and outstanding teacher. He had created rich Anatomical Museum and improved methods for teaching anatomy. His scientific inheritance is contained in 96 publications, among them famous monograph ,,Anthropologic des parties molles”. For investigations on muscles of Negroes he won Prix Broca in 1919. Edward Loth is the founder of Polish Anatomical Society (1923). In thirties he worked as a secretary of Comité International des Recherches sur les Parties Molles (C.LR.P.) residing in Geneva. He took part in many scientific expeditions and travels. During the Second World War prof. Loth was active in defence of Warsaw in 1939 and after that in organization of secret, underground Medical Faculties in Warsaw (1940–1944) where he acted as a professor of anatomy. In 1940 he had organized Institution for Reeducation of Invalids for Polish soldiers wounded in 1939 and guided it until 1944. As a commander of Medical Service of Home Army for Mokotów District he took a part in Warsaw Insurrection and was killed by a bomb in September 15th 1944.